Tapping into the field of foreign language learning games. (3rd December 2012) - Grove, Frederik De; Cornillie, Frederik; Mechant, Peter; Looy, Jan Van
The use of serious games has seen a remarkable growth in the past decade. This has resulted in a substantial number of people with hands–on experience. However, to our knowledge, no research has been performed to harvest this source of information. By means of an explorative study, we collected the opinions of 47 serious game and computer–assisted language learning experts on the potential of serious games for foreign language learning. The first part of this paper discusses the opinions of experts in the light of different perspectives on foreign language learning. The next part of this paper elaborates on a SWOT (strengths, weaknesses, opportunities and threats) analysis of foreign language learning games, resulting in a nuanced view on the opportunities and limitations of foreign language learning games. As such, this paper explores possibilities and limitations regarding language learning games and frames those findings within the boundaries of literature on foreign language learning.